2001
DOI: 10.1016/s0378-1097(01)00354-8
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae pyruvate kinase Pyk1 is PKA phosphorylation substrate in vitro

Abstract: Fractionation of Saccharomyces cerevisiae postribosomal extract on DEAE-cellulose revealed two fractions of cAMP-dependent protein kinase (PKA-1 and PKA-2). The presence of PKA in both fractions was confirmed by immunoblotting with anti-Bcy1 antibodies. Yeast pyruvate kinase Pyk1 identified by amino acid microsequencing analysis and immunoblotting with anti-Pyk1 antibodies copurified with the PKA-1 but not the -2 fraction. Pyk1 can be phosphorylated by yeast PKA in vitro in the presence of cAMP and cGMP. Two-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Preliminary results from Cytryñ ska et al (8) and Rayner et al (9) showed that Pyk1 could be phosphorylated in vitro by Tpk2 and Tpk1, respectively. From our last results and from the results of the immunoprecipitation (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary results from Cytryñ ska et al (8) and Rayner et al (9) showed that Pyk1 could be phosphorylated in vitro by Tpk2 and Tpk1, respectively. From our last results and from the results of the immunoprecipitation (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The stoichiome- tries of phosphorylation attained with C b in vitro are compatible with one phosphorylation site per molecule of pyruvate kinase; however, optimization of the phosphorylation conditions, so as to compensate for the low efficiency usually displayed by PKAs, was not assayed. It has been reported that Pyk1 could be visualized by isoelectric focusing as four different forms with different isoelectric points, suggesting multiple phosphorylation sites per monomer, either under in vitro phosphorylation conditions (8) or analyzing the protein profile from exponentially growing cells (35). In higher eukaryotes at least, several kinases have been reported to be responsible for the multiphosphorylation of pyruvate kinase (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PKA-dependent phosphorylation inhibits the activity of fructose-1,6-bisphosphatase (Fbp1) and stimulates the activity of 6-phosphofructo-2-kinase (Pfk2) and of both isoforms of pyruvate kinase (Pyk1 and Pyk2) (Gancedo et al 1983;Rittenhouse et al 1987;Cytrynska et al 2001;Vaseghi et al 2001;Portela et al 2002;Dihazi et al 2003). Together, these modifications result in the stimulation of glycolysis and the inhibition of gluconeogenesis when glucose is added to glucose-starved cells.…”
Section: Regulation Of the Camp-pka Pathwaymentioning
confidence: 99%
“…Furthermore, PKA directly regulates important metabolic pathways such as glycolysis (6). It phosphorylates proteins catalyzing key enzymatic steps, such as both isoforms of pyruvate kinase, Cdc19 and Pyk2 (13)(14)(15).…”
mentioning
confidence: 99%